GroupBanter: Supporting Serendipitous Group Conversations with IM - Inkpen, Kori; Whittaker, Steven; Czerwinski, Mary; Wallace, James; Fernandez, Roland (The 4th International Conference on Collaborative Computing: Networking, Applications and Worksharing (CollaborateCom 2008), 2008)
This paper describes GroupBanter, a tool for supporting serendipitous group conversations using instant messaging. We investigated the potential of ephemeral group conversations by providing awareness of friends’ IM conversations, serving as an implicit invitation to join a group conversation. We present our vision and describe our prototype system. Results from two field studies carried out in different contexts show that users valued GroupBanter and that it provided new opportunities for communication that aren’t well served by traditional IM, email, or face-to-face communication. Our results indicate there is potential in providing a lightweight communication channel that lies between traditional, private IM conversations and more public IRC-like conversations.